Seasonal dynamics of invertebrates along an altitudinal gradient in a tropical dry scrub [Dinámica estacional de invertebrados en un matorral seco tropical a lo largo de un gradiente altitudinal] - Espinosa íñiguez, C. (2016)
The knowledge of seasonal dynamics of living organisms and their relationships with climatic variables in environmental gradients is needed to understand the possible effects of climate change and contribute to preserve seasonally dry tropical ecosystems. A whole year sampling was carried out with pitfall traps set up in six plots located at different altitudes in a tropical dry scrub to determine whether there were 1) relations among seasonal changes of humidity and daily ranges of temperature and humidity with shifts in number and abundance of taxa, 2) concordance among temporal distribution patterns of communities at different altitudes, 3) influence of altitude on the lengths of periods of abundance of the communities and, 4) influence of altitude on the relationships mentioned in the first goal. Number of taxa correlated negatively with relative humidity and positively with daily thermohygrometic ranges. These correlations were consistent at all altitudes. Abundance only correlated, and negatively, with humidity at two altitudes. With the exception of Diptera, all the correlations of abundance of taxa with humidity were negative. Correlations with daily ranges of temperature and humidity were of different sign. With the exception of Scorpiones, Pseudoescorpiones, Acariformes y Psocoptera all these correlations were consistent at all elevations. The length of periods de abundance did not change with altitude. The temporal distribution of abundances was not concordant among plots. Hence, the results did not give clear proof of climatic variations linked to altitude as responsible of these observed differences in concordance. © 2016 Los Autores.